Paediatric orthopaedics in lockdown: A study on the effect of the SARS-Cov-2 pandemic on acute paediatric orthopaedics and trauma. (17th July 2020) - Baxter, Ian; Hancock, Graeme; Clark, Matthew; Hampton, Matthew; Fishlock, Adelle; Widnall, James; Flowers, Mark; Evans, Owain
Abstract : Aims: To determine the impact of COVID-19 on orthopaediatric admissions and fracture clinics within a regional integrated care system (ICS). Methods: A retrospective review was performed for all paediatric orthopaedic patients admitted across the region during the recent lockdown period (24 March 2020 to 10 May 2020) and the same period in 2019. Age, sex, mechanism, anatomical region, and treatment modality were compared, as were fracture clinic attendances within the receiving regional major trauma centre (MTC) between the two periods. Results: Paediatric trauma admissions across the region fell by 33% (197 vs 132) with a proportional increase to 59% (n = 78) of admissions to the MTC during lockdown compared with 28.4% in 2019 (N = 56). There was a reduction in manipulation under anaesthetic (p = 0.015) and the use of Kirschner wires (K-wires) (p = 0.040) between the two time periods. The median time to surgery remained one day in both (2019 IQR 0 to 2; 2020 IQR 1 to 1). Supracondylar fractures were the most common reason for fracture clinic attendance (17.3%, n = 19) with a proportional increase of 108.4% vs 2019 (2019 n = 20; 2020 n = 19) (p = 0.007). While upper limb injuries and falls from play apparatus, equipment, or height remained the most common indications for admission, there was a reduction in sports injuries (p < 0.001) but an increase in lacerations (p = 0.031). Fracture clinic management changed with 67% (n = 40) of follow-up appointments via telephone and 69% (n = 65) of patients requiring cast immobilization treated with a 3M Soft Cast, enabling self-removal. The safeguarding team saw a 22% reduction in referrals (2019: n = 41, 2020: n = 32). Conclusion: During this viral pandemic, the number of trauma cases decreased with a change in the mechanism of injury, median age of presentation, and an increase in referrals to the regional MTC. Adaptions in standard practice led to fewer MUA, and K-wire procedures being performed, more supracondylar fractures managed through clinic and an increase in the use of removable cast. Cite this article: Bone Joint Open 2020;1-7:424–430.